Repurposing of glycine transport inhibitors for the treatment of erythropoietic protoporphyria. Issue 8 (19th August 2021) - Halloy, François; Iyer, Pavithra S.; Ghidini, Alice; Lysenko, Veronika; Barman-Aksözen, Jasmin; Grubenmann, Chia-Pei; Jucker, Jessica; Wildner-Verhey van Wijk, Nicole; Ruepp, Marc-David; Minder, Elisabeth I.; Minder, Anna-Elisabeth; Schneider-Yin, Xiaoye; et al.
Summary: Erythropoietic protoporphyria (EPP) is a rare disease in which patients experience severe light sensitivity. It is caused by a deficiency of ferrochelatase (FECH), the last enzyme in heme biosynthesis (HBS). The lack of FECH causes accumulation of its photoreactive substrate protoporphyrin IX (PPIX) in patients' erythrocytes. Here, we explored an approach for the treatment of EPP by decreasing PPIX synthesis using small-molecule inhibitors directed to factors in the HBS pathway. We generated a FECH - knockout clone from K562 erythroleukemia cells, which accumulates PPIX and undergoes oxidative stress upon light exposure. We used these matched cell lines to screen a set of publicly available inhibitors of factors in the HBS pathway. Inhibitors of the glycine transporters GlyT1 and GlyT2 lowered levels of PPIX and markers of oxidative stress selectively in K562 11B4 cells, and in primary erythroid cultures from an EPP patient. Our findings open the door to investigation of glycine transport inhibitors for HBS disorders. Graphical abstract: Highlights: New strategy to tackle the rare disease erythropoietic protoporphyria (EPP) Genome-edited K562 cells recapitulate aberrations in heme biosynthesis causing EPP Screening the cells identifies drug-like ligands that lower PPIX levels GLYT1/GLYT2 inhibitors slow PPIX accumulation in patient-derived erythroid cultures Abstract : Erythropoietic protoporphyria is a rare disease caused by lack of ferrochelatase. Patients accumulate protoporphyrin IX in their circulation. F. Halloy et al. genome-edited an erythroleukemic cell line to abolish ferrochelatase expression and screened it with repurposed drugs. Glycine-transport inhibitors reduce protoporphyin IX in these cells and in patient-derived erythroid cultures.